Novel Approaches to Hasten Detection of Pathogens and Antimicrobial Resistance in the Intensive Care Unit - Guillamet, M. Cristina Vazquez; Burnham, Jason P.; Kollef, Marin H. (Seminars in Respiratory and Critical Care Medicine, 2019)
Antibiotic resistance is recognized as a key determinant of outcome in patients with serious infections influencing empiric antibiotic practices especially for critically ill patients. Within the intensive care unit (ICU), nosocomial infections and increasingly community-onset infections are caused by multidrug-resistant bacteria. Escalating rates of antibiotic resistance adds substantially to the morbidity, mortality, and cost related to infections treated in the ICU. Both gram-positive organisms, such as methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci, and gram-negative bacteria, including Pseudomonas aeruginosa, Acinetobacter species, carbapenem-resistant Enterobacteriaceae, and extended spectrum β-lactamase producing organisms, are urgent threats. The rising rates of antimicrobial resistance have resulted in routine empiric administration of broad-spectrum antibiotics by clinicians to critically ill patients even when bacterial infection is microbiologically absent. Moreover, new broad-spectrum antibiotics are a challenge to use effectively while avoiding emergence of further resistance. Use of rapid diagnostic technologies (RDTs) will likely provide an important methodology for achieving this important balance. There is an urgent need for integrating the administration of new and existing antibiotics with RDTs in a way that is safe, cost-effective, applicable in all countries, and sustainable.
Keywords: Antibiotic resistance; microbiology; diagnostics; infections